Kuasa Tubuh dan Perlawanan: Anti Politisasi dan Komodifikasi Tubuh Perempuan dalam Ruang Virtual - Tari Purwanti (Umbara, 2020)
This study discusses the discourse of "self love" as a form of women’s resistance against the politicization of their body in the virtual space, and how biopolitic and propaganda made by Indonesian government to counter pornographic activities in the virtual space. This study  applied qualitative descriptivemethod.  Data were collected through observations and interviews with social media accounts owner  on their actualization of self-love. This study  finds that the practice of anti-politicization  against  female body often misinterpreted  as the practice of self-commodification.   This study also suggest that objectification against women’s body is not always caused by men, but also by women. On the other hand, the state  also has power over the body of its citizens has full control over all of their actions in social media. The state ward off discourses of self-love that lead to self-commodification through various policies and laws.